2009
DOI: 10.1002/ccd.22129
|View full text |Cite
|
Sign up to set email alerts
|

Transradial approach for stenting of vertebrobasilar stenosis: A Feasibility Study

Abstract: VAS and BAS using the transradial approach appear to be safe, technically feasible, and reproducible. Technical ease of cannulation of vertebral artery with IMA guide catheter using ipsilateral transradial approach should make it more convenient when compared with femoral approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Nevertheless, in situations of severe vertebrobasilar insufficiency, angioplasty and stenting of the vertebral artery is warranted. A few reports delineate the safety and efficacy of the TR approach to this intervention . Although no comparative studies are available, stenting of the vertebral artery is best achieved from ipsilateral TR access.…”
Section: Trpi – Technical Considerationsmentioning
confidence: 99%
“…Nevertheless, in situations of severe vertebrobasilar insufficiency, angioplasty and stenting of the vertebral artery is warranted. A few reports delineate the safety and efficacy of the TR approach to this intervention . Although no comparative studies are available, stenting of the vertebral artery is best achieved from ipsilateral TR access.…”
Section: Trpi – Technical Considerationsmentioning
confidence: 99%
“…In Bendok's study, four patients with brachiocephalic ectasia had successful endovascular intervention for intracranial vertebrobasilar stenosis done via the transradial approach [9]. Two other studies also reported technical success in their patients with angioplasty and stenting performed for the treatment of vertebrobasilar stenosis, including a small number of patients with intracranial stenosis [7,8]. However, no selection criteria was mentioned in these studies, and intracranial or extracranial stenosis were not analyzed separately.…”
Section: Discussionmentioning
confidence: 94%
“…artery stemming off from the subclavian artery means that access via the upper limb arteries is a more direct approach and hence an attractive alternative. The transradial approach has already been shown by coronary interventions to have a high success and low complication rate with a reduced length of hospital stay [6], and has been reported to be feasible for intracranial vertebrobasilar interventions by some small case series [7][8][9]. In this study, we aimed to review the experience in our institution of 58 patients using the transradial approach for endovascular treatment of severe intracranial vertebrobasilar stenosis.…”
Section: Introductionmentioning
confidence: 98%
“…3,5,7) Hyperperfusion syndrome has also occurred after treatment for vertebral artery stenosis. 2,12,14) Our review of the literature found only 3 patients with hyperperfusion syndrome after treatment for subclavian artery stenosis. 1,13,15) One patient had been treated with a subclavian-carotid artery bypass, the other 2 had undergone endovascular surgery; cerebral perfusion study of hyperperfusion syndrome was not performed.…”
Section: Discussionmentioning
confidence: 99%